Personal Hygiene of Sonaf Maneka Catholic Orphanage in Kupang City - Faykusa, Delince; Sahdan, Mustakim; Landi, Soleman (Faculty of Public Health, Nusa Cendana University, 2022)
Personal hygiene is an effort made to maintain cleanliness and health of oneself both physically and mentally. Individual hygiene includes bathing behavior, dress behavior, hand washing behavior, dental and mouth care behavior, and hair care behavior. Kupang City in 2018, skin tanners were included in the top 10 diseases with the number of cases 9,562 (5.5%). The purpose of the study is to know the picture of personal hygiene consisting of: habits of bathing, washing hands, cutting nails, caring for teeth and mouth, caring for hair and changing clothes. This type of descriptive research with suvey methods is conducted from April to May 2021. The population is 117 people. Sampling using purpossiv sampling technique so that the sample is 49 people. Catholic Orphanage in Kupang City with good criteria of 85.71%, the habit of changing clothes 63.26% with good criteria, Hand washing The results showed that of 49 respondents who studied the bathing habits of pre-adolescents and adolescents at Sonaf Maneka habits 89.80% with good criteria, nail cutting habits 79.60% with good criteria, ability to care for teeth and mouth 48.98% with sufficient criteria, and the habit of caring for hair 93.87% with good criteria. This research can be concluded that the personal picture of hygiene in Sonaf Maneka Catholic Orphanage in Kupang City in 2021 is good.